PENGARUH IKLIM ORGANISASI DAN PERSEPSI KEADILAN TERHADAP CAREER PLATEAU DENGAN KEPUASAN KERJA SEBAGAI MEDIASI STUDI DI BADAN KEPEGAWAIAN DAERAH PROVINSI JAWA TENGAH - Mayang Saswati, Angky (Students Journal of Economic and Management, 2012)
Human Resource is the basic capital of national development. In carrying out its main task, responsibilities, authority, human resource needs supporting factors such as justice perceptions, organizational climate, job satisfaction and career plateau. The research formulation problem is: 1) Does justice perceptions  affect job satisfaction?; 2) Does organizational climate influence job satisfaction?; 3) Does the justice perceptions affect the career ladder?; 4) Does organizational of climate affect  on the career ladder?; 5) Does job satisfaction affects the career ladder?. Justification (hypothesis) of this research is 1) Justice perceptions positively affect on job satisfaction.; 2) Organizational climate positively influence job satisfaction.; 3) Justice perceptions positively affects on the career ladder.; 4) Organizational climate positively  affect on the career ladder.; 5) Job satisfaction positively affects on the career ladder. The type of the research is descriptive quantitative and use survey as its methods. The data collection method used in this research is giving a list of questions (questionnaire). The data analysis model used is multiple linear regression  analysis. The total sample  114  people  is  all  Employee Staff  Agency of Central Java Province Government The results showed that:1) Justice perceptions of the career plateau is not effectively influenced job satisfaction as the mediation. This means that the indirect effect is more significant than the direct effect.; 2) Organizational climate on the career plateau is very effectively influenced job satisfaction as the mediation. Keywords : Justice perceptions, organizational climate, job satisfaction, career plateau.